Navigating Privacy Concerns: Social Media Users’ Perspectives on Data Sharing - Jafari, MohammadBagher; Shaghaghi, Zahra. (AI and Tech in Behavioral and Social Sciences, 2023)
This study aims to explore social media users’ perspectives on privacy concerns and data sharing, identifying the major themes that encapsulate their experiences and attitudes towards online privacy and the strategies they employ to protect their personal information. A qualitative research design was employed, involving semi-structured interviews with 23 social media users from diverse demographic backgrounds. Thematic analysis was used to analyze the interview transcripts, focusing on identifying and interpreting patterns related to privacy concerns and protective behaviors. The analysis revealed five major themes: Understanding of Privacy, Attitudes Towards Data Sharing, Privacy Management Strategies, Impact of Social Media on Privacy, and Future Perspectives on Privacy. Each theme comprised several categories and concepts, including Definitions of Privacy, Privacy Awareness, Willingness to Share, Risks and Benefits, Use of Privacy Settings, Information Disclosure, Avoidance Behaviors, Perceived Threats, Changes in Behavior, Desired Changes, Predictions about Privacy, and User Empowerment. The study highlights the complex and multifaceted nature of social media users’ privacy concerns and the strategies they adopt to navigate these challenges. It underscores the importance of developing more intuitive privacy controls and the need for ongoing education on privacy management. The findings also suggest a call for social media platforms and policymakers to consider users’ diverse needs and concerns in the development of privacy protection measures.